Augmenting Screw Technique to Prevent TLIF Cage Subsidence: A Biomechanical In Vitro Study - Alina Jacob; Alicia Feist; Ivan Zderic; Boyko Gueorguiev; Jan Caspar; Christian R. Wirtz; Geoff Richards; Markus Loibl; Daniel Haschtmann; Tamas F. Fekete (Bioengineering)
(1) Cage subsidence in spine surgery is a frequent clinical challenge. This study aimed to assess a novel screw augmentation technique for Transforaminal Lumbar Interbody Fusion in cadavers of reduced bone mineral density (BMD). (2) Forty human lumbar vertebrae (BMD 84.2 ± 24.4 mgHA/cm3, range 51–119 mgHA/cm3) were assigned to two groups: augmenting screw group and control group. The augmentation technique comprised placement of two additional subcortical screws. Ten constructs per group were loaded with a quasi-static load-to-failure protocol and other ten were cyclically loaded. Failure modes were documented. (3) During the quasi-static load-to-failure testing, the augmenting screw technique showed a significantly higher failure load (1426.0 ± 863.6 N) versus the conventional technique in the control group (682.2 ± 174.5 N, p = 0.032). Cyclic loading revealed higher number of cycles and corresponding load until reaching 5 mm subsidence and significantly higher number of cycles and corresponding load until reaching 10 mm subsidence for the augmenting screw technique (9645 ± 3050; 1164.5 ± 305.0 N) versus the conventional technique in the control group (5395 ± 2340; 739.5 ± 234.0 N, p < 0.05). Failure modes were different and showed bending of the augmenting screws, followed by cut-out. (4) The investigated augmenting screw technique demonstrated higher failure loads and cycles to failure against cage subsidence compared to conventional cage placement. Failure modes were different between the two techniques and may lead to a different kind of complications.